2014
DOI: 10.14423/smj.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Can α-Lipoic Acid Mitigate Progression of Aging-Related Decline Caused by Oxidative Stress?

Abstract: Aging is progressively deteriorating physiological function that leads to increasing risks of illness and death. Increases in life expectancy and the aging of a large segment of the population have made age-related disability and morbidity increasingly important issues. Supplements such as α-lipoic acid may have antiaging effects by positively affecting oxidative stress, cognitive function, and cardiovascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Oxidative stress has been identified as a key factor associating obesity with related disorders such as cardiovascular diseases or type 2 diabetes mellitus, which can be triggered by a high-level consumption of several macronutrients: glucose, SFAs or omega-6 polyunsaturated fatty acids (n-6 PUFA) inducing inflammation through nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) mediated pathways [102]. Contrariwise a large body of research has investigated the potential beneficial effect of dietary antioxidants such as vitamin A, vitamin E, vitamin C, selenium, α-lipoic acid, resveratrol and other polyphenols in the prevention of metabolic and age-related chronic diseases [103,104,105].…”
Section: Nutrients Oxidative Stress and Nafld/nashmentioning
confidence: 99%
“…Oxidative stress has been identified as a key factor associating obesity with related disorders such as cardiovascular diseases or type 2 diabetes mellitus, which can be triggered by a high-level consumption of several macronutrients: glucose, SFAs or omega-6 polyunsaturated fatty acids (n-6 PUFA) inducing inflammation through nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) mediated pathways [102]. Contrariwise a large body of research has investigated the potential beneficial effect of dietary antioxidants such as vitamin A, vitamin E, vitamin C, selenium, α-lipoic acid, resveratrol and other polyphenols in the prevention of metabolic and age-related chronic diseases [103,104,105].…”
Section: Nutrients Oxidative Stress and Nafld/nashmentioning
confidence: 99%
“…Several studies have demonstrated the antioxidant, anti-inflammatory, and hypoglycemic properties of ALA [1215]. Furthermore, ALA has been shown to have a positive effect on the OxS linked with aging [16]. For this reason, the aim of the present study was to determine the effect of 600 mg/day of ALA on some markers of OxS and inflammation and RAGE in older adults with T2DM.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, in a large, cross-sectional study of healthy women, healthy eating patterns were not associated with a lower level of oxidative stress, which was measured using fluorescent oxidation products as global markers of oxidative stress [86]. A large body of research has also investigated the potential beneficial effect of dietary antioxidants, such as olive oil, a greater ratio of omega-3/omega-6 PUFAs, polyphenols, carotenoids, and high-fiber foods, which may ameliorate oxidative stress in NAFLD [87][88][89].…”
Section: Therapeutic Approach To Reducing Oxidative Stress In Nafldmentioning
confidence: 99%